Quality of life of elderly with diabetic foot problem / Fatin Farhana Abdul Majid, Nur Masturah Abdul Manaff and Nurul Fazlin Mohd Ismail. - Abdul Majid, Fatin Farhana; Abdul Manaff, Nur Masturah; Mohd Ismail, Nurul Fazlin (2015)
Background: Diabetes Mellitus (DM) is one of the many chronic diseases in the world. The most common complication of DM is diabetic neuropathy where the most common type is diabetic peripheral neuropathy (DPN). Patients with DPN who usually have diabetic foot problems are unaware of the signs and symptoms which usually affect their sensorimotor e.g. pain. Therefore, quality of life of an elderly with diabetes is expected to be affected. Objectives: This research aimed to determine the quality of life (QoL) of elderly with diabetic foot problem, to examine the relationship between QoL and demographic data of elderly with diabetic diabetic foot problem and also to examine the relationship between QoL and clinical characterises of elderly with diabetic foot problem. Method: This research revolves around cross sectional study that was conducted in General Wards and Outpatient Clinics in Hospital Tuanku Ampuan Rahimah (HTAR). The QoL was assessed by using NeuroQoL questionnaire that had already been translated from English language to Malay language. The questionnaire had been distributed and answered by elderly with diabetic foot problem of age 60 years and above. The overall description of QoL among elderly with diabetic foot problem reports were identified by using descriptive statistic and the correlation between QoL, demographic data and clinical characteristics of elderly with diabetic foot problem were examined by using parametric test. Results: Elderly with diabetic foot problem have fair QoL 56.5% (n=70). There was significant difference with living status and QoL [F (2,121) = 6.592, p=0.002]. Tukey HSD post-hoc test showed that living with spouse/friends has better QoL compared to living with children. There were also significant difference between diabetes duration and QoL (r= -0.242, p=0.007) and between treatments and QoL [F (3,120) =3.465, p=0.018]. As diabetes duration increased, the QoL will decreased and Tukey HSD of post-hoc test for treatments showed that elderly who took OHA and insulin have lower QoL compared to whom taking OHA only. Conclusion: Special interventions should be developed to improve QoL of elderly with diabetic foot problem. A high risk group of elderly who lived alone, had longer diabetes duration and had received combination of treatments of diet control, oral medication and insulin should be given specific nursing care so that can elevate their QoL. Detail assessment especially on pain and emotional distress must be done to help in improving QoL.